Where age doesn’t matter: no relative age effects in esports at the professional level - Laxdal, Aron; Erikstad, Martin Kjeøen (Frontiers in Sports and Active Living, 2025)
Relative age effects (i.e., a systematic bias favouring individuals born earlier in the selection year) have been found in many traditional sports, especially among younger athletes in sports where physical maturation (e.g., increased size and strength) is advantageous. The aim of this study was to explore relative age effects in professional esports, which differ from traditional sports in some key areas. The birth months of 15,734 e-sport athletes playing ten different games were collected from Liquipedia and analyzed using chi-square tests. The analyses showed no practically meaningful relative age effects among the athletes, indicating that being relatively older does not yield advantages in gameplay. The same results applied across the various age groups as well as the different game types. This lack of relative age effects can likely be attributed to the cognitive and skill-based nature of esports, as well as the flexible and online nature of competitive environments in this domain